THE MAIN PROBLEMS OF THE STUDENTS’ ELECTRONIC PORTFOLIO FORMATION IN TERMS OF THE HIGHER EDUCATIONAL PROGRAMS - Yulia V. Dementieva (Образование и наука)
The aim of the study is the description of the main problems of formation of the student’s electronic portfolio in the conditions of realization of Federal State Educational Standards of the Higher Education (FSES of HE).Methods.Theoretical analysis of scientific literature concerning the subject under discussion; monitoring of existing practices in modern Russian Universities procedures for the formation and maintenance of students electronic portfolio.Results. The author describes the main problems of the electronic students’ portfolio formation; some ways of solving described problems are offered.Scientific novelty concludes in the formation of key ideas of the electronic students’ portfolio based on the understanding of requirements of Federal State Educational Standards of Higher Education for the results of mastering educational programs. They are the formation of general cultural, general professional and professional competences.Practical significance. The researching results will become the theoretical basis for the systematic organization of the process of creating and maintaining an electronic students’ portfolio during the whole period of their studying at the university; the researching results can become a basis for methodological developments.